Korean Historical Records on Halley’s Comet Revisited - Ki-Won Lee; Byeong-Hee Mihn; Young Sook Ahn (Journal of Astronomy and Space Sciences, 2014)
In this paper, we report the analysis of Korean historical records on the periodic Halley’s comet according to the period (i.e., the Three Kingdoms, Goryeo Dynasty, and Joseon Dynasty) using various sources such as the Samguksagi (The History of the Three Kingdoms), Goryeosa (The History of the Goryeo Dynasty), and Joseonwangjosillok (The Annals of the Joseon Dynasty). With regards to the apparition time of the comet for each return, we referred to the works of Kronk. For the Three Kingdoms period, we could not find any record relevant to Halley’s comet from the Samguksagi. Furthermore, we examined the suggestion that the phenomenon of “two Suns” which appeared on April 1, 760 (in a luni-solar calendar), as recorded in the Samgukyusa (The Legends and History of the Three Kingdoms), indicates an instance of the the daytime appearance of Halley’s comet. In contrast with the Three Kingdoms period, we found that all returns of Halley’s comet are recorded during the Goryeo Dynasty, although others have questioned some accounts. We also found that the appearance of Halley’s comet in 1145 is mentioned in a spirit-path stele made in 1178. For the Joseon Dynasty period, we found that all apparitions of the comet are recorded, as with the Goryeo Dynasty, except for the return of 1910, at which time the former dynasty had fallen. In conclusion, we think that this study will be helpful for understanding Korean historical accounts on Halley’s comet.